Potential of SARS-CoV-2 to Cause CNS Infection: Biologic Fundamental and Clinical Experience - Huang, Jianhan; Zheng, Meijun; Tang, Xin; Chen, Yaxing; Tong, Aiping; Zhou, Liangxue (Frontiers in Neurology, 2020)
Abstract SARS-CoV-2 is a novel coronavirus leading to serious respiratory disease and is spreading around the world at a raging speed. Recently there is emerging speculations that the central nervous system (CNS) may be involved during SARS-CoV-2 infection, contributing to the respiratory failure. However, the existence of viral replication in CNS has not been confirmed due to the lack of evidence from autopsy specimens. Considering the tropism of SARS-CoV-2, ACE2, is prevailing in CNS, and the neuroinvasive property of human coronavirus was widely reported, there is a need to identified the possible complications during COVID-19 for CNS. In this review, we conduct a detailed summary for the potential of SARS-CoV-2 to infect central nervous system from latest biological fundamental of SARS-CoV-2 to the clinical experience of other human coronaviruses. To confirm the neuro-invasive property of SARS-CoV-2 and the subsequent influence on patients will require further exploration by both virologist and neurologist.